Evaluating rural tourism competitiveness: Application of PROMETHEE-GAIA method - Esther Sri Astuti Soeryaningrum Agustin; Rina Martini; Budi Setiyono (Cogent Economics & Finance)
This study aims to analyze the factors that determine rural tourism competitiveness in Indonesia, measure the tourism competitiveness in each rural tourism, and discover the gap between rural tourism in four provinces. This study adopts the Travel and Tourism Competitiveness Report (TTCR) Model from the World Economic Forum, and we develop the combination between the PROMETHEE method and GAIA plane. This study finds that Giri Emas is rural tourism with the highest score of competitiveness index compared to others. Generally, the tourism sector potential in Indonesia is great and must be developed with additional sense of policy to have a better performance. Stakeholders need to give attention to the Health and Hygiene sub-pillar to be ready during pandemic and post-pandemic. This study encourages policymakers to develop an appropriate strategy that can make the performance of the tourism sector better. Managerial implications are that rural tourism needs to approach various aspects other than the tourist attraction factors. Policymakers should give priority to health facilities and capacities as part of the pandemic response. This study measures the tourism competitiveness of villages with semi-structured interviews and questionnaires. Therefore, it will portray a more detail tourism in Indonesia.